NEW CHARACTERIZATION OF 2-PRE-HILBERT SPACE - Malčeski, Samoil; Anevska, Katerina; Malčeski, Risto (Matematichki Bilten, 2014)
The problem of finding necessary and sufficient conditions a 2-normed space to be treated as 2-pre-Hilbert space is the focus of interest of many mathematicians. Few characterizations of 2-inner product are given in [1], [3], [5], [6], [8] and [9]. In this paper a new necessary and sufficient condition for existence of 2-inner product into 2-normed space is given.